USE OF MINERALIZED WATERS FOR IRRIGATION OF THE TERRITORY OF UZBEKISTAN - Berdiev Shavkat Zhuraevich; Sarmonov Nodirbek Utkir ugli (Galaxy International Interdisciplinary Research Journal, 2021)
The first two years, experimental fields of 4 hectares were prepared to study the technique of irrigation along furrows with one-time on medium-sagging and two-time compaction of the bottom furrows with the wheels of the T-28x4 tractor according to a specially proposed scheme (Fig. 1). The main purpose of this experiment is to determine the possibility of reducing water absorption into the furrow and, consequently, to reduce the depth water loss, to reduce the roughness of the furrow to accelerate the flow of the jet to the end of the furrow, which would make it possible to maintain the uniformity of the distribution of subsidence along the length of the field and reduce the influence of individual local subsidence on the process of water absorption into the soil. The next stage of work was the following activities. On an experimental plot of 20 hectares, experimental plots were laid with proposals for a watersaving irrigation method (Fig. 2), sown with a pre-zoned cotton variety T-108, with corn - Uzbek tooth-shaped, alfalfa - Ashgabat. The uniformity of moistening along the length of the distribution of costs with a constant diameter of the holes is achieved by compaction lying under the hoses and pipes under its own weight and the weight of water in them, reducing the absorption when searching for soil particles, excess water that has not been absorbed at the beginning of the field flows down along the furrow bed and before moisturizing the end portions of obtuse furrows. On slopes above 0.01, a relative uniformity of water distribution is achieved.